The microbial models of molecular biology from genes to genomes - Davis, Rowland H. (Oxford Oxford University Press, 2003)
Explains the role of simple biological model systems in the growth of molecular biology. This book presents the history of molecular biology, tracing the work in bacteriophages in E coli, the role of other prokaryotic systems, the protozoan and algal models, and the move into eukaryotes with the fungal systems - Neurospora, Aspergillus and yeast.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Molecular biology -- History; Molecular genetics -- History; Microbial genetics -- History; Molecular microbiology -- History; Electronic books; Electronic books